2007
DOI: 10.1007/s00586-007-0422-y
|View full text |Cite
|
Sign up to set email alerts
|

The validity of multimodal intraoperative monitoring (MIOM) in surgery of 109 spine and spinal cord tumors

Abstract: In a prospective study of 109 patients with tumor of the spine MIOM was performed during the surgical procedure between March 2000 and December 2005. To determine the sensitivity and specificity of MIOM techniques used to monitor spinal cord and nerve root function during surgical procedure of spinal tumors. MIOM become an integrated procedure during surgical approach to intramedullar and extramedullar spine tumors. The combination of monitoring ascending and descending pathways may provide more sensitive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 18 publications
1
30
0
1
Order By: Relevance
“…The high sensitivity and specificity of MIOM during the different surgical procedures as presented in this supplement [10][11][12][28][29][30][31] document its advantages. It has been clearly shown that MEP monitoring improves outcome after surgery for intramedullary spinal tumors [27].…”
Section: Indications For Multimodal Intraoperative Monitoringmentioning
confidence: 75%
“…The high sensitivity and specificity of MIOM during the different surgical procedures as presented in this supplement [10][11][12][28][29][30][31] document its advantages. It has been clearly shown that MEP monitoring improves outcome after surgery for intramedullary spinal tumors [27].…”
Section: Indications For Multimodal Intraoperative Monitoringmentioning
confidence: 75%
“…1,2,17 In particular, transcranial electrical stimulation motor evoked potentials (TcMEPs) are widely used for intraoperative spinal cord monitoring. Monitoring of TcMEPs became the gold standard due to their increased sensitivity and the importance of motor function.…”
mentioning
confidence: 99%
“…LR between 1 and 2 and between 0.5-1 rarely alter pretest probability. 6 Despite traditional spinal IOM literature suggests that NIOM is effective in identifying patients at a high risk for sustaining new spinal cord injuries [7][8][9][10][11][12][13][14][15] as well as animal research has supported human experience, [16][17][18] there is a heterogeneity in IOM services and this should be reviewed to see what accounts for the difference in false-positive and false-negative cases in the literature.…”
Section: Resultsmentioning
confidence: 99%